A novel biodegradable stent applicable for use in congenital heart disease: Bench testing and feasibility results in a rabbit model. Issue 3 (8th August 2013) - Veeram Reddy, Surendranath R.; Welch, Tre R.; Wang, Jian; Bernstein, Frederic; Richardson, James A.; Forbess, Joseph M.; Nugent, Alan W.
<x xml:space="preserve">Abstract</x> Objectives A novel double opposed helical (DH) biodegradable stent was designed and fabricated for CHD applications. The primary objective was to evaluate the feasibility of DH stent delivery and deployment in rabbit external iliac arteries (EIA). Secondary objectives were to assess stent patency, thrombosis and inflammation at 1‐week and 1‐month follow‐up. Background Biodegradable stents have largely been designed for adult cardiovascular indications, to avoid long term complications of permanent implants. A growing child with congenital heart disease (CHD) would especially derive substantial benefit from this technology. Methods DH stents were manufactured to 3, 4, 5, and 6‐mm diameter with poly‐l‐lactic acid (PLLA) fibers. Bench test analysis was performed. Six DH stents were implanted in rabbit EIA. Vessel patency was assessed at 1‐week and 1‐month follow‐up with repeat angiography, intravascular ultrasound (IVUS). Histopathological evaluation was performed. Results The elastic recoil and collapse pressure of DH stents were comparable to conventional metal stents. All DH stents were successfully delivered and implanted with good apposition to the vessel wall and no collapse of the proximal, mid or distal ends. All stented vessels remained patent. No acute or early stent thrombosis was noted. Histopathology showed minimal inflammatory response and mild neointimal proliferation at 1 month follow‐up. Conclusions In vitro results of DH PLLA biodegradable stents are comparable to conventional metal stents. The pilot animal study confirms the delivery and deployment of the DH stents to the desired location. The DH design can be used to fabricate larger diameter stents needed for CHD. © 2013 Wiley Periodicals, Inc.